Demand for Family Planning Among Voluntary Counseling and Testing Women Clients in Public Health Facilities, Dawuro Zone, South West Ethiopia: A Cross Sectional Study - Hailu, Haimanot Ewnetu; Tesfaye, Thomas; Alemseged, Fessahaye (International Journal For Research In Health Sciences And Nursing, 2019)
Background:The total demand for family planning is the sum of the percentage of women using family planning and the percentage of women with unmet need for family planning.Both unintended pregnancy and HIV infection can be protected by a number of ways. Access to HIV/AIDS services without access to Sexual and Reproductive Health services and vice versa can have adverse effects on community health and stop the progress of advances made against HIV/AIDS, unmet Family Planning need, and maternal mortality.In developing countries the provision of family planning services at voluntary counseling and testing settings is low. There is lack of information on demand for family planning among women voluntary counseling and testing clients in the study area. Therefore the study aimed to assess demand for family planning among voluntary counseling and testing clientwomen in South West Ethiopia. Methods:Facility based cross sectional study was conducted on total of 401 respondents consecutively. Descriptive, bivariate and multivariable analyses were performed. Statistical significance was declared at a value of p < 0.05. Result:Demand for family planning among voluntary counseling and testing women client was 71.5% in the study area. Marital status (AOR= 0.17; 95% CI: 0.04, 0.67), income level (AOR= 2.44; 95%CI: 1.34, 4.45) and live birth (AOR= 3.27; 95% CI: 1.35, 7.92) were predictors of demand for family planning. Conclusion:The finding showed that majority of women voluntary counseling and testing clients had demand for family planning. Factors affecting demand for family planning was marital status, level of income and having given live birth. Hence, providing family planning services continuously at VCT settings is recommended.